(3eLed GdCUhd aj CMcGe GdfLhes - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3Efi LeYJ ai gPG GdcJGH ef CUhd UfGYg GdCMcGe s
(3BNQgG (B:s
(3hdG JYLd HGdMce EdG HYO GdacQg GdWhjdg hGdfXQ GdcHjQ hGdJCed GdTGai s
(3ajgG HYV GdLOGhds
(3cGf GdeDda MjkG MhGdi Sfg (B350 (3g`s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B222 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B94 s
Keywords: (3Gdadcs